Karakteristik Ulkus Diabetikum Pada Penderita Diabetes Melitus - Ade Utia Detty; Neno Fitriyani; Toni Prasetya; Brigita Florentina (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Diabetes mellitus has a variety of chronic complications and the most frequently encountered is a diabetic ulcer. The incidence of diabetic ulcers annually is 2% among all patients with diabetes and 5-7.5% among diabetic patients with peripheral neuropathy. Objective: To understand the characteristics of diabetic ulcers in diabetes mellitus patients in RSUD Dr. H. Abdul Moeloek Lampung in 2018. Research Method: This research is a type of descriptive research. The sampling technique used in this research is a total sampling. Result: From the 119 patients, the majority of diabetic ulcer patients is in the late elderly ages which about 55 peoples, based on gender are female with a total of 71 peoples, based on their family history of the disease, there is a family history of the disease as many as 101 peoples, based on length of hospitalization, it is at most 0-5 days with a total of 94 peoples, based on therapy, the most is with surgical procedures with a total of 98 peoples. Conclusion: The characteristics of diabetic ulcers are dominated by women in late elderly ages and the average ulcer patient has a family history of diabetes mellitus, they are treated at 0-5 days, and the therapy is used with surgery